Effects of Long Term Debt to Total Assets, Short Term Debt to Total Assets, Total Asset Turnover, and Inventory Turnover on Profitability of Manufacturing Companies in Consumer Goods Subsector Listed on IDX - Stefani Chandra; Cindy Juliawati (Journal of Applied Business and Technology, 2020)
This research aims to determine the effects of solvability and activity on profitability of manufacturing companies in consumer goods subsector in Indonesia. The dependent variable used was ROA, while the independent variables included, LTDTA, STDTA, TATO and ITO. The population consisted of 53 manufacturing companies in consumer goods subsector listed on Indonesia Stock Exchange. Samples were selected using purposive sampling. Out of 53 companies, 2 companies have been delisted from 2014 to 2018, 14 new companies were listed on the Indonesia Stock Exchange after 2014 and 1 companies have not published financial reports. Hence, the samples used in this research were only 36 companies. The method used was linear regression. The result showed that LTDTA has a significant negative effect on ROA, on the contrary STDTA, TATO and ITO do not have significant effect on ROA.